KONTRIBUSI POSITIF ORIENTALISME: KAJIAN ATAS REINHART DOZY (1820-1883 M) - Ghulam Falach (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2020)
The main focus of Orientalist thought is nothing but to reconstruct and influence Islamic civilization. Their enthusiasm to activate orientalism is increasingly challenged by the presence of Islam as a religion that has followers of most of the world's population. One of the actions of orientalism towards the Islamic world is to start a research movement on the Qur'an and al-Hadith which are the basis of the law and guidelines of Muslims. Not far from the critics of the Qur'an and al-Hadith, they also deconstructed aspects of the development of science, Islamic law, and even the originality of Islamic history. Some famous orientalism figures, one of them is Reinhart Dozy, a famous orientelism from the Netherlands with the concept of literacy in the history of Islamic civilization in Spain. Even though he received a lot of criticism and appreciation from both orientalists and Muslim thinkers, his literary work has had a great influence on Islamic civilization. The discussion steps of this study are entirely carried out using qualitative research that is library research. To be more useful and function properly, this paper is equipped with an explanation using the method of description, interpretation and analysis of data in each discussion. This is done, none other than to focus the discussion to produce a consistent and comprehensive understanding.